Preclinical models of endometriosis and interstitial cystitis/bladder pain syndrome: an Innovative Medicines Initiative-PainCare initiative to improve their value for translational research in pelvic pain. Issue 9 (September 2021) - Nunez-Badinez, Paulina; De Leo, Bianca; Laux-Biehlmann, Alexis; Hoffmann, Anja; Zollner, Thomas M.; Saunders, Philippa T.K.; Simitsidellis, Ioannis; Charrua, Ana; Cruz, Francisco; Gomez, Raul; Tejada, Miguel Angel; McMahon, Stephen B.; et al.
Abstract : Abstract: Endometriosis (ENDO) and interstitial cystitis/bladder pain syndrome (IC/BPS) are chronic pain conditions for which better treatments are urgently needed. Development of new therapies with proven clinical benefit has been slow. We have conducted a review of existing preclinical in vivo models for ENDO and IC/BPS in rodents, discussed to what extent they replicate the phenotype and pain experience of patients, as well as their relevance for translational research. In 1009 publications detailing ENDO models, 41% used autologous, 26% syngeneic, 18% xenograft, and 11% allogeneic tissue in transplantation models. Intraperitoneal injection of endometrial tissue was the subcategory with the highest construct validity score for translational research. From 1055 IC/BPS publications, most interventions were bladder centric (85%), followed by complex mechanisms (8%) and stress-induced models (7%). Within these categories, the most frequently used models were instillation of irritants (92%), autoimmune (43%), and water avoidance stress (39%), respectively. Notably, although pelvic pain is a hallmark of both conditions and a key endpoint for development of novel therapies, only a small proportion of the studies (models of ENDO: 0.5%-12% and models of IC/BPS: 20%-44%) examined endpoints associated with pain. Moreover, only 2% and 3% of publications using models of ENDO and IC/BPS investigated nonevoked pain endpoints. This analysis highlights the wide variety of models used, limiting reproducibility and translation of results. We recommend refining models so that they better reflect clinical reality, sharing protocols, and using standardized endpoints to improve reproducibility. We are addressing this in our project Innovative Medicines Initiative-PainCare/Translational Research in Pelvic Pain. Abstract : Supplemental Digital Content is Available in the Text.